The role of investments for the economy of the Russian Federation - Kabanov Oleg Vladimirovich, Sergushina Elena Sergeevna,; Nikolaevna, Ermakova Marina; Chandra, Ram; Aleksandrovich, Guryanov Sergey; Markaryan, Varvara Raphaelovna (Opción, 2020)
The article analyzes the concept of investments, their forms, types, as well as the impact on the economic climate in the country via comparative quantitative research methods. As a result, the characteristic of the structure of the main investing countries in the economy of Russia, the recipient countries of direct investments from the Russian Federation is given and a high percentage of the process of investing in a country is the returning capital of organizations from abroad. In conclusion, investments are the lever of progressive formation and positive actions for economic processes in the country.